Pergerseran Hukum Islam dari Reduksionis ke Sintesis: Telaah Pemikiran Ziauddin Sardar - Khusniati Rofi'ah (Justicia Islamica, 2011)
Should be rocognized that the Islamic world faced with stagnation or failure to comply with the role of ijtihad. This era of stagnation began after a period of codification (asr al-tadwin) as the emergence of a dogmatic assumption that the achievements of the classical scholars (mujtahid) has been final, so no longer need a renewal of thought. So there was a shift in mindset, from ijtihadi pattern to taqlidi pattern. According to Ziauddin Sardar, There are several reasons that cause the failure of muslims to answer the call of ijtihad. One of them is that the majority of muslims place sharia/Islamic law on the position of the holy (sacred shariah), and they reduce the meaning of shari'a itself and other Islamic concepts.